Kontribusi Jumlah Kehamilan (Gravida) Terhadap Komplikasi Selama Kehamilan dan Persalinan - Sulastri Sulastri; Arina Maliya; Ni'mah Mufidah; Eka Nurhayati (Indonesian National Nurses Association (INNA) of Central Java, 2019)
Introduction. Obstetric and neonatal emergencies are a condition that can be life threatening and can occur both during pregnancy and childbirth. One of the causes of emergency is the complication of pregnancy, where this complication can arise due to risk factors during pregnancy, one of which is the gravida. Pregnant women with primigravida and gravida = 4 are high-risk factors for pregnancy and childbirth. The purpose of this study was to determine the contribution of the number of pregnancies (gravida) to mothers who had complications of pregnancy and childbirth in the work area of the Gatak Health Center, Sukoharjo. Methods. This research is a quantitative descriptive with a retrospective approach, data collection using the record or other documents in the form of health information for pregnant women with pregnancy comorbidities taken based on data from January 1 to December 31, 2018, in total sampling. Result. Of the 224 data of pregnant women with comorbidities, among them experienced pre-eclampsia (67.1%). The characteristics of respondents were based on the most age at 20-35 years old (82.5%), multigravida status (84.8%), and SC delivery (67%). Discussion. The importance of regulating and monitoring the number of pregnancies (gravida) of mothers to prevent complications of pregnancy and childbirth and to improve the degree of life of a mother.